2018
DOI: 10.1264/jsme2.me17052
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Bacterial Community in Biofilms for Degradation of Poly(3-Hydroxybutyrate-<i>co</i>-3-Hydroxyhexanoate) Films in Seawater

Abstract: Microplastics are fragmented pieces of plastic in marine environments, and have become a serious environmental issue. However, the dynamics of the biodegradation of plastic in marine environments have not yet been elucidated in detail. Polyhydroxyalkanoates (PHAs) are biodegradable polymers that are synthesized by a wide range of microorganisms. One of the PHA derivatives, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) has flexible material properties and a low melting temperature. After an incubation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…Few studies have investigated the biodegradation of plastics through biofilm formation in aqueous environments. We previously demonstrated that one of the PHA derivatives, poly(3-hydroxybutyrate- co -3-hydroxyhexanoate) (PHBH), was degraded by the formation of a biofilm on its surface in seawater samples ( 9 ). Microplastic pollution has become a serious global issue not only in seawater, but also in freshwater environments ( 17 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have investigated the biodegradation of plastics through biofilm formation in aqueous environments. We previously demonstrated that one of the PHA derivatives, poly(3-hydroxybutyrate- co -3-hydroxyhexanoate) (PHBH), was degraded by the formation of a biofilm on its surface in seawater samples ( 9 ). Microplastic pollution has become a serious global issue not only in seawater, but also in freshwater environments ( 17 ).…”
mentioning
confidence: 99%
“…The biodegradability in freshwater of six types of general biodegradable plastic films: poly(lactic acid) (PLA), poly(butylene adipate- co -terephthalate) (PBAT), polybutylene succinate (PBS), poly(butylene succinate- co- butylene adipate) (PBSA), poly(ɛ-caprolactone) (PCL), and PHBH, was assessed ( 9 ). Biofilms were formed on plastic surfaces using a previously described method with slight modifications ( 9 ). Briefly, all plastic films had a thickness of approximately 100 μm, and were prepared by T die cast extrusion.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Acidovorax and Undibacterium were isolated from the biofilm as PHBH degraders. In contrast to seawater experiments (Morohoshi et al, 2018a), they found biofilm formation on the PBS, PBSA, and PBAT films (but not on PLA). Although the degradation of these polymers was not observed, these findings strongly indicate that bioplastics are more easily deteriorated in freshwater environments than in seawater environments.…”
mentioning
confidence: 58%